2021
DOI: 10.2967/jnumed.121.262426
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 68Ga-FAPi-46 PET Biodistribution with FAP Expression by Immunohistochemistry in Patients with Solid Cancers: Interim Analysis of a Prospective Translational Exploratory Study

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 20 publications
3
62
0
Order By: Relevance
“…FAP expression in healthy tissues is negligible. ( 12,13,16,17 ) We have recently reported the discovery of OncoFAP, the small molecule FAP-targeting agent with the highest affinity reported so far. ( 18 ) Proof-of-concept targeting studies with [ 68 Ga]Ga-OncoFAP-DOTAGA ( 68 Ga-OncoFAP), a PET tracer based on OncoFAP, have confirmed excellent biodistribution in patients with different primary and metastatic solid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…FAP expression in healthy tissues is negligible. ( 12,13,16,17 ) We have recently reported the discovery of OncoFAP, the small molecule FAP-targeting agent with the highest affinity reported so far. ( 18 ) Proof-of-concept targeting studies with [ 68 Ga]Ga-OncoFAP-DOTAGA ( 68 Ga-OncoFAP), a PET tracer based on OncoFAP, have confirmed excellent biodistribution in patients with different primary and metastatic solid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…The origin, number, and distribution of FAP-expressing CAFs as well as the number of FAP molecules per cell may differ among tumors. Mona et al [20] reported the presence of a strong association between tumor 68 Ga-FAPI uptake intensity and histopathological FAP expression in colon cancer. We expected variations in intratumoral tracer distribution in treatment-naïve patients with speci c histopathologic types of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…This case suggests that the expression of FAP in hormone-sensitive organs such as the breast and uterus may undergo a physiological increase after pregnancy and during lactation (133). The latest study by Christine E. Mona et al showed that the highest 68 Ga-FAPI-46 PET signal in the normal organ was the bladder due to the urinary bladder due to urinary excretion and the uterus due to normal myometrial FAP expression (134).…”
Section: Uterusmentioning
confidence: 98%
“…The latest study by Christine E. Mona et al. showed that the highest 68 Ga-FAPI-46 PET signal in the normal organ was the bladder due to the urinary bladder due to urinary excretion and the uterus due to normal myometrial FAP expression ( 134 ).…”
Section: Pelvic Organsmentioning
confidence: 99%